MANUSCRIPT STUDY OF THE HIKAYAT BANJAR : EXCAVATION OF ISLAMIC HISTORICAL SOURCES OF THE ARCHIPELAGO - Munadi, Fathullah; Ilhami , Hamidi (Pascasarjana UIN ANTASARI Banjarmasin, 2021)
The Hikayat Banjar manuscript is an ancient handwritten manuscript that contains important historical information to be studied. This manuscript is key in the study of the social history of the Banjar kingdom and in this research is used as the main material for exploring the Islamic history of the archipelago. The research on the Hikayat Banjar manuscript can be considered to bring new nuances to the discourse on the history of Islam in the archipelago. This research is a qualitative study using a philological approach in which researchers will conduct manuscript inventory, manuscript description, manuscript & text comparison, to present text editing before analyzing it. Since in this research the Hikayat Banjar is positioned as a source of Islamic history, the researcher seeks to examine in detail Islamic data related to normative teachings and Islamic culture which can then be translated into an analysis of social history and the history of Islamic institutions. From the research on these 2 reviews of the Hikayat Banjar, Islamic factors were found in the form of; 1) Arabic words or sentences and, 2) There is Islamic content in the arrangement of the Hikayat Banjar episodes which are detailed in the following phases; a) Pre-Islamic phase b) Introduction of Islam phase c) Formation phase of Islam in the Banjar Kingdom, and d) Post-Islamization phase, and 3) The Walisongo story in the Hikayat Banjar.